A Modeling of Voltage Protection Variation System Number of KWH Meter Rotation - Joseph Damanik; Putri Delima Manurung; Solly Aryza (CERED Indonesia Institute, 2024)
The main difference between prepaid and postpaid electricity lies in the payment method. As the name implies, 'postpaid' means paid after use. While 'prepaid', paid or purchased before use. This study is a comparison between Postpaid kwh meters and Prepaid kwh meters with the use of varying loads with voltage reduction treatment with a voltage of 230 volts, 220 volts, 198 volts and 165 volts. In the varying loads in the kwh meter rotation test, the prepaid rotation speed is longer than the postpaid rotation speed with a difference of 0.53 hours or 32 minutes. While in the Energy-saving lamp (LHE) load, the study found a very significant difference from the kwh meter rotation with a voltage of 198 Volts and the LHE load for 3.53 hours or 212 minutes between prepaid and postpaid, so prepaid is better than postpaid.